1998
DOI: 10.1046/j.1365-2249.1998.00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased CD4 and increased CD8 counts with T cell activation is associated with chronic helminth infection

Abstract: We have previously reported the presence of marked immune dysregulation with a dominant Th2 profile, in a population of Ethiopian immigrants (ETH) in Israel heavily infected with helminths. In order to characterize better this immune dysregulation we studied by flow cytometry the expression of several activation markers on peripheral T cell populations, and lymphocyte apoptosis, in blood samples obtained from 63 'new' ETH (recently arrived), 18 'old' ETH (> 5 years since immigration) and 34 non-Ethiopian Israe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
126
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(150 citation statements)
references
References 51 publications
(46 reference statements)
21
126
1
2
Order By: Relevance
“…Impairment of T-helper cell function appears to be a constitutive feature of GD, since it is not affected by disease severity, effectiveness of treatment, previous splenectomy, or other features. Low CD4+ cell count is a hallmark of chronic inflammatory diseases, such as HIV infection (Catalfamo et al 2011) and chronic parasitic infestations (Kalinkovich et al 1998), and may result from an increased rate of apoptosis in the CD4+ cell compartment, something already described in chronic immune stimulationassociated diseases and conditions (Jelley-Gibbs et al 2005). …”
Section: Discussionmentioning
confidence: 98%
“…Impairment of T-helper cell function appears to be a constitutive feature of GD, since it is not affected by disease severity, effectiveness of treatment, previous splenectomy, or other features. Low CD4+ cell count is a hallmark of chronic inflammatory diseases, such as HIV infection (Catalfamo et al 2011) and chronic parasitic infestations (Kalinkovich et al 1998), and may result from an increased rate of apoptosis in the CD4+ cell compartment, something already described in chronic immune stimulationassociated diseases and conditions (Jelley-Gibbs et al 2005). …”
Section: Discussionmentioning
confidence: 98%
“…Studies relating AIDS patients to opportunistic infections have shown that HAART has contributed to HIV infection control and to the reconstitution of patient immune systems, leading to a reduction in the occurrence of opportunistic infections, including those caused by intestinal parasites (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition has a serious influence on immunity aspects, including the production of cytokines and antibodies, particularly Th2 profile (21)(22)(23). Recent research has also reported that intestinal helminth infections result in immune responses that involve cytokines produced by Th2 cells, with IgE production, eosinophilia, and mastocytosis (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in PBMC composition, with an increase in the number of CD8 ϩ cells and a decrease in the number of CD4 ϩ cells, have been observed in individuals with general immune activation caused by persistent helminthic infection (13,16).…”
Section: Discussionmentioning
confidence: 99%